PENGARUH SALES PROMOTION DAN KERAGAMAN PRODUK PADA SHOPEE TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Muhammad Shendy Alvian; Bulan Prabawani (Universitas Diponegoro, 2020)
We can feel the changes of people lifestyle nowadays in this modern era. One of that is about shopping activities. The technology development makes people easier to get what they need. The digitalization evolution has caused the rapid growth of the marketplaces. One of them is Shopee, which is the leading marketplace in Southeast Asia and Taiwan. However, Shopee unable to compete with other marketplaces such as Tokopedia and Lazada, with the decreasing number of visitors on Shopee Indonesia.This study aims to determine the effect of sales promotion and product diversity on repurchase intention through customer satisfaction. This type of research is explanatory research. Samples were taken from 100 respondents who had made purchases on Shopee. The sampling techniques was purposive sampling. The data was analyzed using SPSS 23.0 for Windows. The results showed that sales promotion and product diversity have a positive influence on repurchase intention through customer satisfaction. From intervening variable test, it showed that customer satisfaction had a partial mediating effect between sales promotion and product diversity on repurchase intention.